Prove \[{{\text{x}}^2} - {y^2} = {a^2} - {b^2}\], if \[x = a\sec \theta + b\tan \theta \] and \[y = a\tan \theta + b\sec \theta \].
Answer
Verified
482.7k+ views
Hint: Here we will substitute the value of x and y on the left hand side of the equation and prove it equal to the right hand side using various trigonometric identities:-
\[
1 + {\tan ^2}\theta = {\sec ^2}\theta \\
\Rightarrow {\sec ^2}\theta - {\tan ^2}\theta = 1 \\
\]
\[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\]
Complete step-by-step answer:
The given equation is:-
\[{{\text{x}}^2} - {y^2} = {a^2} - {b^2}\]
Let us consider the left hand side of the given equation:-
\[LHS = {{\text{x}}^2} - {y^2}\]
Now it is given that:-
\[x = a\sec \theta + b\tan \theta \] and \[y = a\tan \theta + b\sec \theta \]
Hence putting in the respective values of x and y in LHS we get:-
\[LHS = {\left( {a\sec \theta + b\tan \theta } \right)^2} - {\left( {a\tan \theta + b\sec \theta } \right)^2}\]
Now applying the following identity on both he terms:-
\[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\]
We get:-
\[LHS = {\left( {a\sec \theta } \right)^2} + {\left( {b\tan \theta } \right)^2} + 2\left( {a\sec \theta } \right)\left( {b\tan \theta } \right) - \left[ {{{\left( {a\tan \theta } \right)}^2} + {{\left( {b\sec \theta } \right)}^2} + 2\left( {b\sec \theta } \right)\left( {a\tan \theta } \right)} \right]\]
Now simplifying it further we get:-
\[
LHS = {a^2}{\sec ^2}\theta + {b^2}{\tan ^2}\theta + 2ab\sec \theta \tan \theta - \left[ {{a^2}{{\tan }^2}\theta + {b^2}{{\sec }^2}\theta + 2ab\sec \theta \tan \theta } \right] \\
\Rightarrow LHS = {a^2}{\sec ^2}\theta + {b^2}{\tan ^2}\theta + 2ab\sec \theta \tan \theta - {a^2}{\tan ^2}\theta - {b^2}{\sec ^2}\theta - 2ab\sec \theta \tan \theta \\
\]
Now cancelling the required terms we get:-
\[LHS = {a^2}{\sec ^2}\theta + {b^2}{\tan ^2}\theta - {a^2}{\tan ^2}\theta - {b^2}{\sec ^2}\theta \]
Now taking \[{a^2}\] and \[{b^2}\] common we get:-
\[LHS = {a^2}\left( {{{\sec }^2}\theta - {{\tan }^2}\theta } \right) - {b^2}\left( {{{\sec }^2}\theta - {{\tan }^2}\theta } \right)\]
Again taking common we get:-
\[LHS = \left( {{{\sec }^2}\theta - {{\tan }^2}\theta } \right)\left( {{a^2} - {b^2}} \right)\]
Now applying the following identity:-
\[
1 + {\tan ^2}\theta = {\sec ^2}\theta \\
\Rightarrow {\sec ^2}\theta - {\tan ^2}\theta = 1 \\
\]
We get:-
\[
\Rightarrow LHS = \left( {{a^2} - {b^2}} \right) \\
{\text{ }} = RHS \\
\]
Therefore,
\[LHS = RHS\]
Hence proved.
Note: The student may make mistakes while applying the identity, so the identity should be first simplified in the required form and then apply it.
The student can also use the following identity on the initial stage:
\[{a^2} - {b^2} = \left( {a + b} \right)\left( {a - b} \right)\]
Hence,
\[{{\text{x}}^2} - {y^2} = \left( {x + y} \right)\left( {x - y} \right)\]
Then put in the values of x and y and proceed further to get the desired answer.
\[
1 + {\tan ^2}\theta = {\sec ^2}\theta \\
\Rightarrow {\sec ^2}\theta - {\tan ^2}\theta = 1 \\
\]
\[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\]
Complete step-by-step answer:
The given equation is:-
\[{{\text{x}}^2} - {y^2} = {a^2} - {b^2}\]
Let us consider the left hand side of the given equation:-
\[LHS = {{\text{x}}^2} - {y^2}\]
Now it is given that:-
\[x = a\sec \theta + b\tan \theta \] and \[y = a\tan \theta + b\sec \theta \]
Hence putting in the respective values of x and y in LHS we get:-
\[LHS = {\left( {a\sec \theta + b\tan \theta } \right)^2} - {\left( {a\tan \theta + b\sec \theta } \right)^2}\]
Now applying the following identity on both he terms:-
\[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\]
We get:-
\[LHS = {\left( {a\sec \theta } \right)^2} + {\left( {b\tan \theta } \right)^2} + 2\left( {a\sec \theta } \right)\left( {b\tan \theta } \right) - \left[ {{{\left( {a\tan \theta } \right)}^2} + {{\left( {b\sec \theta } \right)}^2} + 2\left( {b\sec \theta } \right)\left( {a\tan \theta } \right)} \right]\]
Now simplifying it further we get:-
\[
LHS = {a^2}{\sec ^2}\theta + {b^2}{\tan ^2}\theta + 2ab\sec \theta \tan \theta - \left[ {{a^2}{{\tan }^2}\theta + {b^2}{{\sec }^2}\theta + 2ab\sec \theta \tan \theta } \right] \\
\Rightarrow LHS = {a^2}{\sec ^2}\theta + {b^2}{\tan ^2}\theta + 2ab\sec \theta \tan \theta - {a^2}{\tan ^2}\theta - {b^2}{\sec ^2}\theta - 2ab\sec \theta \tan \theta \\
\]
Now cancelling the required terms we get:-
\[LHS = {a^2}{\sec ^2}\theta + {b^2}{\tan ^2}\theta - {a^2}{\tan ^2}\theta - {b^2}{\sec ^2}\theta \]
Now taking \[{a^2}\] and \[{b^2}\] common we get:-
\[LHS = {a^2}\left( {{{\sec }^2}\theta - {{\tan }^2}\theta } \right) - {b^2}\left( {{{\sec }^2}\theta - {{\tan }^2}\theta } \right)\]
Again taking common we get:-
\[LHS = \left( {{{\sec }^2}\theta - {{\tan }^2}\theta } \right)\left( {{a^2} - {b^2}} \right)\]
Now applying the following identity:-
\[
1 + {\tan ^2}\theta = {\sec ^2}\theta \\
\Rightarrow {\sec ^2}\theta - {\tan ^2}\theta = 1 \\
\]
We get:-
\[
\Rightarrow LHS = \left( {{a^2} - {b^2}} \right) \\
{\text{ }} = RHS \\
\]
Therefore,
\[LHS = RHS\]
Hence proved.
Note: The student may make mistakes while applying the identity, so the identity should be first simplified in the required form and then apply it.
The student can also use the following identity on the initial stage:
\[{a^2} - {b^2} = \left( {a + b} \right)\left( {a - b} \right)\]
Hence,
\[{{\text{x}}^2} - {y^2} = \left( {x + y} \right)\left( {x - y} \right)\]
Then put in the values of x and y and proceed further to get the desired answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE